Екологічна естетика як філософія гармонії між людиною та природою - Сулацкова, Ольга; Sulatskova, Olga (Східноєвропейський національний університет імені Лесі Українки, 2014)
Здійснено аналіз екологічної естетики, яка обґрунтовує естетичну цінність природи, досліджує естетичні стани людини у взаємодії з нею, визначається як філософія гармонії між людиною і природою, що виникає в певному контексті культури. The analysis of ecological aesthetics, which grounds the aesthetically beautiful value of nature, probes the aesthetically beautiful consisting of man of co-operating with it, is carried out in the article, it is determined as philosophy of harmony between a man and nature which arises up in the certain context of culture. Concluded that reducing the aesthetic value of the natural object only through economic expediency is immoral. Because the beauty in nature or art as essentially good, what is our moral duty. That is why environmental aesthetics very necessary today for the formation of ecological culture. In fact, according to one of the definitions of culture and environmental culture is a voluntary limit yourself, your nature, for the sake of preserving the ecology of the environment. Therefore a mechanism is effects of artistic images of nature on emotion and a sense of personality formation in it on this basis of aesthetic attitude to the natural environment, and through him-ecological thinking and environmental consciousness, because only they are the basis of ecological-ethical and eco-responsible human activity.
Ecological Aesthetics as Philosophy o Harmony is Between Man and Nature
Keywords: екологія; культура; естетика; екологічна естетика; екологічна культура; ecology; culture; aesthetics; ecological aesthetics; ecological culture